Humidity, Temperature and Carbon Monoxide Detection Instrument in the Air Using Lcd Monitor and Microcontroller - Ardi, Syahril; Hidayat, M; Adrian, Moch Gito (Journal of Asian Scientific Research, 2012)
The humidity, temperature, and carbon monoxide detection instrument are used for safety of factory environment because the excessive of humidity, temperature, and carbon monoxide can endanger condition in the factory. While we use SHT1 1 sensor from Sensirion to detect the humidity and temperature, we use TGS5042 sensor from Figaro to detect the carbon monoxide. In this detection instrument, there are some components for maximizing the performance, i.e. relay that connected to buzzer as alarm. This alarm will be active if the humidity, temperature, and carbon monoxide are excessive in the air. In addition, we use LCD (Liquid Crystal Display; 4 x 20) and LCD (Liquid Crystal Display) monitor as a result display from all sensors detection. MicroVGA is used as connector between microcontroller and LCD monitor. TGS5042 sensor needs time for producing the voltage while starting until the stable position. This research provides significant benefits for health and safety system environments because the concentration levels of carbon monoxide (CO), humidity and temperature data in the form of numbers or letters will be shown via LCD or PC (Personal Computer). If the levels of carbon monoxide (CO), humidity and temperature exceed the maximum or minimum value has been determined then it will display a warning buzzer alarm.